Designing A Religious Moderation Learning Model for Islamic Early Childhood Education - Saugi, Wildan; Susmiyati, Sri; Zurqoni, Zurqoni; Maesaroh, Dwi Titi (JURNAL PENDIDIKAN USIA DINI, 2026)
Religious moderation is increasingly emphasized in Islamic early childhood education (PAUD/RA), yet teachers often lack practical, age-appropriate steps to translate values such as cooperation, peaceful conflict resolution, and respect for differences into daily learning. This study aimed to develop a contextual learning model to support religious moderation instruction in an Islamic PAUD setting. Using Plomp’s (2013) Educational Design Research framework, the study proceeded through preliminary research, prototyping, and assessment. It was conducted at RA Pesantren Ilmu Al-Qur’an, Kutai Timur Regency, East Kalimantan, involving the school head, teachers, and children selected purposively. Data were gathered through classroom observations, semi-structured interviews, and document analysis of lesson plans (RPPH), teaching materials, and learning media. The resulting prototype organises learning into five steps: problem orientation using topics or objects close to children’s lives; story presentation drawing on the Qur’an, Hadith, and scholars’ exemplars; message discussion; contextualisation to everyday situations; and reflection and conclusion. Expert validation involved three experts in early childhood education, religious moderation, and learning design, and the results indicated high feasibility across content feasibility, language, presentation, and graphics (4.50–4.58; M = 4.54/5). The experts recommended deeper reflective prompts, richer early childhood–appropriate examples of cooperation across differences, a greater variety of learning media, and more inclusive graphics; all recommendations were incorporated into the revised model. The model provides a classroom-ready flow and an observation tool covering tolerance, collaboration, anti-violence, and respect for differences; broader trials are recommended to test effectiveness and further validate the instrument.